A Preliminary Study: The Effect of Slow Deep Breathing Exercise (SDBE) on Resting Heart Rate and Respiration Rate of Hypertension Patients - Candrawati Susiana; Oktaviana Husnul Afifah Rizky; Bening Ati Viva Ratih; Mustofa Mustofa (E3S Web of Conferences)
The prevalence of hypertension in Indonesia increases with age. Examination of vital signs such as resting pulse and respiratory rate are parameters of hypertension morbidity. One alternative therapy for hypertension is slow, deep breathing exercises. This study aimed to determine the effect of slow, deep breathing exercises on hypertensive patients' resting heart rate and respiratory rate. The research design used was pre-experimental with one group pretest and posttest on 26 hypertensive patients at Posyandu Lansia Waras Winangun, Banyumas. The sampling method used was the total sampling technique. Participants were treated with slow, deep breathing exercises three times a week for six weeks. Resting heart and respiratory rates were examined before and after the intervention of slow, deep breathing exercises. Data analysis of the results in this study used the Wilcoxon non-parametric test. Slow deep breathing exercises significantly decreased resting heart rate (p=0.001), but the respiratory rate was not found to decrease significantly (p=0.209). It can be concluded that the administration of slow, deep breathing exercises affected the resting heart rate but did not affect the respiration rate.